Hubungan Kemandirian Dengan Risiko Jatuh Pada Lansia Di Wilayah Kerja Puskesmas Megang Kota Lubuklinggau Tahun 2025 - Eva Susanti; Danur Azissah; Sasteri Yulianti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
In general, someone who enters old age experiences changes. These changes can be seen from physical changes in hair, face, hands, changes in the five senses, decreased vision, hearing and motor skills. These changes can affect the decline in daily activities. The purpose of this study was to determine the relationship between independence and the risk of falling in the elderly in the Megang Community Health Center Working Area of ​​Lubuklinggau City in 2025. The research method used was descriptive research with a cross-sectional approach. The sampling technique used Purposive Sampling technique with a sample size of 59 elderly people. The results of the univariate test analysis showed that almost half of the respondents (42.4%) were dependent on independence, and almost half of the respondents (37.3%) were at high risk of falling. The results of the bivariate analysis obtained the relationship between independence (p = 0.000) and the risk of falling in the elderly. There is a relationship between independence and the risk of falling in the elderly in the Megang Community Health Center Working Area, Lubuklinggau City in 2025. Researchers suggest that respondents can maintain or increase independence through routine physical activity, maintaining a balanced nutritional intake, and using assistive devices if necessary.